Desain Media Pembelajaran Berbasis Model Creative Problem Solving untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis - Zendrato, Yohana; Telaumbanua, Yakin Niat (Indo-MathEdu Intellectuals Journal, 2022)
Mathematics is a subject that must be learned by students. However, there are still many obstacles in the learning process because students are not able to learn independently, lack of learning media in learning mathematics. The development model used is the ADDIE model. The first stage is the analysis stage (analyze) where researchers conduct curriculum analysis, needs analysis, and analysis of student characteristics through observations and interviews with subject teachers. In the second stage is the design stage where researchers design learning media designs as math learning media. The third stage is development where researchers validate the learning media design, which is validated by experts, from this assessment it can be seen whether the learning media design developed by researchers is valid or not. The implementation stage is carried out to test the practicality of the learning media design. The fifth stage is the evaluation stage, researchers give tests to students to see the effectiveness of the product. Based on the research results, the mathematics learning media design developed has been tested very valid by material expert validators with a percentage of 96%, language experts with a percentage of 98%, media experts with a percentage of 92%, the level of practicality with an average percentage of 88% and the effectiveness level of 73,81